Combining ability studies in groundnut (Arachis hypogaea L.) genotypes: COMBINING ABILITY STUDIES IN GROUNDNUT GENOTYPES - M VAITHIYALINGAN (Journal of Oilseeds Research, 2016)
Combining ability analysis was carried out for 24 hybrids developed through line x tester mating design in groundnut. Non-additive gene action was predominant for all the characters studied. Based on the mean gca effects parents viz., JL 777, RG 426 and JDR 66 could be selected for crossing programme to obtain yield improvement. Among the crosses, R 2001-3 x R 2001-2 registered significant sca effects. Hence pedigree breeding method could be adopted to isolate desirable recombinants. Crosses viz., JL777 x R 2001-2 and JL777 x RG 426 could be exploited for recombination breeding.